Mutants of E. coli heat labile toxin act as effective mucosal adjuvants for nasal delivery of an acellular pertussis vaccine: differential effects of the non-toxic AB complex and enzyme activity on Th1 and Th2 cells - MILLS, KINGSTON (American Society for Microbiology, 1999)
Mucosal delivery of vaccines is dependent on the identification of safe and effective adjuvants that can enhance the immunogenicity of protein antigens administered by nasal or oral routes. In this study we demonstrate that two mutants of Escherichia coli heat-labile toxin (LT), LTK63, which lacks ADP-ribosylating activity, and LTR72, which has partial enzyme activity, act as potent mucosal adjuvants for the nasal delivery of an acellular pertussis (Pa) vaccine. Both LTK63 and LTR72 enhanced antigen-specific serum immunoglobulin G (IgG), secretory IgA, and local and systemic T-cell responses. Furthermore, using the murine respiratory challenge model for infection with Bordetella pertussis, we demonstrated that a nasally delivered diphtheria, tetanus, and acellular pertussis (DTPa) combination vaccine formulated with LTK63 as an adjuvant conferred a high level of protection, equivalent to that generated with a parenterally delivered DTPa vaccine formulated with alum. This study also provides significant new information on the roles of the binding and enzyme components of LT in the modulation of Th1 and Th2 responses. LTK63, which lacks enzyme activity, promoted T-cell responses with a mixed Th1?Th2 profile, but LTR72, which retains partial enzyme activity, and the wild-type toxin, especially at low dose, induced a more polarized Th2-type response and very high IgA and IgG antibody titers. Our findings suggest that the nontoxic AB complex has broad adjuvant activity for T-cell responses and that the ADP-ribosyltransferase activity of the A subunit also appears to modulate cytokine production, but its effect on T-cell subtypes, as well as enhancing, may be selectively suppressive.
PUBLISHED
Keywords: Biochemistry